MULTICULTURAL PERSPECTIVE ON THE MOTIVATION OF STUDENTS IN TEACHING PHYSICAL EDUCATION - Peter Kaylene; Tressa Lawrence Rosone (Jurnal Ilmiah Peuradeun, 2016)
With the rollover of a new century, society in America has become more dynamic. These changes in student demographics throughout the U.S. have spawned an increased need for awareness by teachers for their students’ needs across curriculums. This study examined attitudes of high school students toward fitness and sports activities taught in physical education, and the perceived effectiveness of their physical education curriculum for improving their fitness and skill levels. This research has focused on providing teachers with multicultural training with the hope that through this training, teachers will convey the importance of respect and sensitivity for all cultures to their students. Overall, successful physical education teachers in the culturally diverse school setting (e.g., urban schools) tend to maintain high expectations for student accomplishment, provide the best possible learning environments, and implement activities that aid increased student involvement.